METHOD DEVELOPMENT AND IMPLEMENTATION SPATIAL PLAN OF THE CITY (Municipal economy of cities. Series: «Economy science», 2013)
The problems of changing approaches to urban planning documentation in the application of strategic planning methods of territories. A method of developing and implementing the new instrument of urban development – spatial plan of the city.